2019
DOI: 10.1371/journal.pone.0220741
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime abuse and somatic symptoms among older women and men in Europe

Abstract: Background Research suggests that survivors of interpersonal violence have an increasing experience of bodily symptoms. This study aims to scrutinise the association between lifetime abuse and somatic symptoms among older women and men, considering demographics/socio-economic, social support and health variables. Methods A sample of 4,467 community-dwelling persons aged 60–84 years (57.3% women) living in seven European countries (Germany, Greece, Italy, Lithuania, Port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
2
12
0
1
Order By: Relevance
“…It is also important to distinguish health consequences of elder abuse from natural processes related to ageing and diseases. 31 There are different types of comorbidities in both groups. They have a higher rate of peripheral artery disease (34.9%), stroke or TIA (11.3%), as well as of degenerative neuromuscular diseases (30.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to distinguish health consequences of elder abuse from natural processes related to ageing and diseases. 31 There are different types of comorbidities in both groups. They have a higher rate of peripheral artery disease (34.9%), stroke or TIA (11.3%), as well as of degenerative neuromuscular diseases (30.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Lifetime abuse could result in somatic symptoms in old age, independent of a particular disease. It is also important to distinguish health consequences of elder abuse from natural processes related to ageing and diseases . There are different types of comorbidities in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic dysregulation (i.e., impairment in or pain related to basic bodily functions) was included in this domain based on to evidence that children may express emotional distress indirectly through somatic complaints and somatoform symptoms (Agnafors et al, 2019;Flaherty , 2013;Ford et al, 2013b;Vernberg et al, 2011). In addition, adults (Eslami et al, 2019;Littleton, 2015;Paras et al, 2009) and adolescents (Bonvanie et al, 2015;Espejo-Siles et al, 2020;Nixon et al, 2011;Rey et al, 2020) with a history of childhood sexual abuse or peer victimization are at risk for stress-related somatic complaints and bodily problems (i.e., functional gastrointestinal disorders, chronic nonspecific and pelvic pain, psychogenic seizures). Dissociation, which may occur either as psychological (e.g., depersonalization, derealization, alter personality states) or somatoform (e.g., unexplained paralysis or sensory experiences) symptoms, also was included in the DTD affect/somatic dysregulation domain, based on evidence that severe emotion dysregulation (e.g., alexithymia; impaired modulation of and recovery from extreme negative emotion states) is related to pathological dissociation in childhood (Hebert et al, 2020) and adulthood (Ford & Gomez, 2015;Powers et al, 2015;Van Dijke et al, 2010).…”
Section: Criteria For Developmental Trauma Disordermentioning
confidence: 99%
“…An explanation for the opposite directions of the studies may be related to the cultural and social characteristics. A study that included seven European countries found that the perception of health differs among countries and that geographic location was positively associated with somatic symptoms, with coming from Lithuania and Portugal being among the risk factors for the development of symptoms [ 23 ]. “Thus, somatic presentations can be viewed as expressions of personal suffering inserted in a cultural and social context” [ 24 ] (p. 310).…”
Section: Introductionmentioning
confidence: 99%
“…This study was aimed to examine the relationship between health conditions (which included health perception, mental health, and physical and social functioning), psychopathological symptoms, sociodemographic characteristics (i.e., gender, age, and educational level), and FSS. According to our observations as professionals working in health services in Portugal, in addition to the findings of studies that have shown the relationship between FSS and this set of factors [ 8 , 13 , 14 , 23 , 25 ], we hypothesized that individuals with FSS would be mostly female, with a lower educational level and older age. We also hypothesized that the severity of FSS would be associated with the presence of psychopathological symptoms, as well as FSS would be negatively correlated with health conditions.…”
Section: Introductionmentioning
confidence: 99%